2022
DOI: 10.3390/s22030745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DEM Super-Resolution Methods Based on Interpolation and Neural Networks

Abstract: High-resolution digital elevation models (DEMs) play a critical role in geospatial databases, which can be applied to many terrain-related studies such as facility siting, hydrological analysis, and urban design. However, due to the limitation of precision of equipment, there are big gaps to collect high-resolution DEM data. A practical idea is to recover high-resolution DEMs from easily obtained low-resolution DEMs, and this process is termed DEM super-resolution (SR). However, traditional DEM SR methods (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…To demonstrate the effectiveness of the proposed DSMSR, it was compared with the traditional bilinear interpolation algorithm (BL) and four widely used deep learning-based SR models (i.e., SRCNN, SRGAN, ESRGAN, and MA-GAN). SRCNN, SRGAN, and ESRGAN have been employed in the DEM super-resolution [9,24,25,27,56], and they were retrained using the DSM data from this experiment. discriminator remain relatively stable, indicating that the training has achieved a favorable Nash equilibrium and resulting in a satisfactory trained DSMSR.…”
Section: A Experimental Designmentioning
confidence: 99%
“…To demonstrate the effectiveness of the proposed DSMSR, it was compared with the traditional bilinear interpolation algorithm (BL) and four widely used deep learning-based SR models (i.e., SRCNN, SRGAN, ESRGAN, and MA-GAN). SRCNN, SRGAN, and ESRGAN have been employed in the DEM super-resolution [9,24,25,27,56], and they were retrained using the DSM data from this experiment. discriminator remain relatively stable, indicating that the training has achieved a favorable Nash equilibrium and resulting in a satisfactory trained DSMSR.…”
Section: A Experimental Designmentioning
confidence: 99%
“…More recently, a number of sophisticated deep learning artificial intelligence models, such as deep residual networks [22], Recursive Sub-Pixel Convolutional Neural Networks [23], Laplacian of Gaussian Super-resolution [24], Reconstruction Network Combining Internal and External Learning [25], Super-Resolution with Generative Adversarial Network [26] have been proposed. These methods are mostly based on approaches proposed for image super-resolution [22][23][24][25][26]. The result shows that the DEM accuracy has improved regarding root mean square error (RMSE) and the closeness to the reference data [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance perception, Ledig et al [20] integrated a perceptual loss function with a generative adversarial network for SR. Given the distinct characteristics of DEM data compared to natural images, Zhang and Yu [21] applied SRGAN, ESRGAN, and CEDGAN to DEM SR, and the experimental results showed that SRGAN was the most effective in terms of extracting terrain features, outperforming other GANs. This result suggests that neural networks with superior performance in the CV domain might not be equally effective when extracting topographic features.…”
Section: Introductionmentioning
confidence: 99%